Transformation of Labor Market Infrastructure under the Influence of Artificial Intelligence - Zub Mariya Ya. (Bìznes Inform, 2020)
The purpose of the article is to substantiate the development of a timely policy for the transformation of labor market infrastructure in the regions of Ukraine under the influence of artificial intelligence. The article discusses the theoretical features of the concept of «artificial intelligence». Three categories of artificial intelligence are distinguished: artificial narrow intelligence (ANI), which specializes in decision-making in only one area; artificial general intelligence (AGI), which reaches and exceeds the level of ordinary human consciousness; artificial super intelligence (ASI), which is smarter than all of humanity put together. The analysis of basic global risks of the nearest decade is conducted, the spectrum of threats is exposed from the point of view of business-leaders on the way of the economy growing in Ukraine and world. The basic constituent elements of politics of transformation of infrastructure of labor market for the regions of Ukraine, able to redistribute the freed workers, soften the negative consequences of transitional period, warn the swift height of unemployment and and ensure the rapid spread of benefits. The article examines the main trends in the development of the labor market infrastructure under the influence of artificial intelligence. A list of professions in demand for the next 10 years is presented. Competencies for employees in the regions of Ukraine for the future are determined. The definition of the concept "artificial intelligence" is proposed. On the basis of the multifaceted introduction of artificial intelligence in the regional economy, the expediency of developing a model of the infrastructure of systems for the innovative development of the regional labor market in Ukraine is substantiated.